Drug Use Trajectories After a Randomized Controlled Trial of MTFC: Associations with Partner Drug Use - Rhoades, Kimberly A. (2014)
Trajectories of drug use were examined in a sample of women with prior juvenile-justice system involvement. One hundred fifty-three young women who participated in a randomized controlled trial of Multidimensional Treatment Foster Care (MTFC) in adolescence were assessed on five occasions over a 24-month period in young adulthood (mean age = 22.29 years at T1). Participants assigned to the MTFC condition during adolescence reported greater decreases in drug use than girls assigned to the treatment as usual (TAU) condition. Partner drug use was significantly associated with women’s concurrent drug use, although participants in the MTFC condition were more resilient to partner drug use than in the TAU condition. Implications for drug use prevention and intervention programs during adolescence are discussed.